Atropisomeric Hydrogen Bonding Control for CO2 Binding and Enhancement of Electrocatalytic Reduction at Iron Porphyrins. Issue 50 (7th October 2020) - Gotico, Philipp; Roupnel, Loïc; Guillot, Regis; Sircoglou, Marie; Leibl, Winfried; Halime, Zakaria; Aukauloo, Ally
Abstract: The manipulation of the second coordination sphere for improving the electrocatalytic CO2 reduction has led to breakthroughs with hydrogen bonding, local proton source, or electrostatic effects. We have developed two atropisomers of an iron porphyrin complex with two urea functions acting as multiple hydrogen‐bonding tweezers to lock the metal‐bound CO2 in a similar fashion found in the carbon monoxide dehydrogenase (CODH) enzyme. The αα topological isomer with the two urea groups on the same side of the porphyrin provides a stronger binding affinity to tether the incoming CO2 in comparison to the αβ disposition. However, the electrocatalytic activity of the αβ atropisomer outperforms its congener with one of the highest reported turnover frequencies at low overpotential. The strong H/D kinetic isotope effect (KIE) observed for the αα system indicates the existence of a tight water hydrogen‐bonding network for proton delivery which is disrupted by addition of an acid source. The small H/D KIE for the αβ isomer and the enhanced electrocatalytic performance on addition of stronger acid indicate the free access of protons to the bound CO2 on the opposite side of the urea arm. Abstract : Adapting the 3D topological layout of an iron porphyrin catalyst bearing urea groups as multipoint hydrogen‐bonding donors in the second sphere can induce a switch from higher affinity for CO2 binding to faster reaction rate for the CO2 electrocatalytic reduction to CO.